Model Pengembangan Produktivitas dan Kemandirian Masyarakat Akademik Berbasis Akuaponik di Universitas Bangka Belitung - Andri Kurniawan; Robin Robin; Endang Bidayani; Ardiansyah Kurniawan; Ahmad Fahrul Syarif; Denny Syaputra; Eva Prasetiyono; M.A. Hari Fitriyanto (LPPM UNIVERSITAS DIAN NUSWANTORO, 2022)
The challenges faced by the world of education such as universities are not only producing graduates who have good intellectuality, mentality, and morality, but also high productivity and independence. Aquaponics-based aquaculture activities are one of the models that can be developed as a pilot project in the development of productivity and independence of the academic community. This community service activity aimed to present a model in the Program Hilirisasi Produktif (PHP) that can be implemented within the University of Bangka Belitung in particular and the academic community at large. This activity was carried out through an analysis of strength, weaknesses, opportunity, and threat, the stages of preparation of facilities and infrastructure for the application of aquaponics-based aquaculture techniques, the stages of program implementation, and the stages of results evaluation. The activities that have been carried out within a period of three months have produced juvenile of catfish, tilapia fish, broodstock of tilapia, and kangkung vegetables (Ipomea reptans Poir). The sustainability of this activity is very important to make aquaponics-based aquaculture become an effort to produce an independent community in the food sector.